"We don't want to hear about discrimination": Evidence slippage and evidence invention in the politics of foreign credential recognition in Canada. (30th August 2019) - Rivas‐Garrido, Camila; Koning, Edward Anthony
Abstract: This article investigates how Canadian politicians engaged with evidence on foreign credential recognition in 2009. We find that some evidence receives decreasing attention over time, that some politicians bring forward explanations that have nothing to do with the evidence, and that most politicians hold the same position before and after the process of evidence‐gathering. These findings cast doubt on the extent to which politicians use evidence to inform their position on immigration‐related issues, even when they explicitly solicit it. Sommaire: Cet article explore la façon dont les politiciens canadiens ont pris en compte les preuves de reconnaissance des titres de compétences étrangers en 2009. Nous constatons qu'au fil du temps, des preuves font l'objet de moins en moins d'attention, que certains politiciens fournissent des explications n'ayant rien à voir avec les preuves, et que la plupart des politiciens soutiennent la même position avant et après le processus de collecte de preuves. Ces conclusions laissent planer un doute sur l'importance accordée par les politiciens à l'utilisation des preuves pour s'informer sur les questions liées à l'immigration, même lorsqu'ils les sollicitent ouvertement.